THE INFLUENCE OF WORK ABILITY AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE AT PT. PATRA UTAMA MANDIRI - Fauzan Muhammad Oceano (JOSAR (Journal of Students Academic Research), 2023)
The purpose of this study was to determine the effect of work ability and organizational culture partially and simultaneously on employee performance at PT. Patra Utama Mandiri. The sample used is as many as 109 (one hundred and nine) people who are employees at PT. Patra Utama Mandiri. Analysis of the data using multiple linear regression equations and the proof of the hypothesis by using the t test, F test and the coefficient of determination (R2). The results of the t-test of the work ability variable have a negative effect on employee performance at PT. Patra Utama Mandiri. Organizational culture variables have a significant effect on employee performance at PT. Patra Utama Mandiri. The results of statistical tests (F test), simultaneously work ability and organizational culture have a significant effect on employee performance at PT. Patra Utama Mandiri. Based on the t and F tests, the hypothesis is accepted.